The Genetics of Sleep Disorders in Humans: Narcolepsy, Restless Legs Syndrome, and Obstructive Sleep Apnea Syndrome - Caylak, Emrah (Wiley, 2009)
Sleep disorders are a group of neurological disorders known to cause public health problems associated with interference with daily activities including cognitive problems, poor job performance and reduced productivity. There is strong evidence emerging for the presence of genes influencing sleep disorders, such as narcolepsy (NRCLP), restless legs syndrome (RLS), and obstructive sleep apnea syndrome (OSAS). NRCLP is typically characterized by excessive daytime sleepiness, cataplexy, sleep paralysis and hallucinations. RLS is manifested by compelling need to move the legs and usually experienced when trying to sleep. OSAS is major sleep problem characterized by recurrent episodes of upper airway collapse and obstruction during sleep. In the recent years, many research groups have attempted to identify the susceptibility and candidate genes for NRCLP, RLS, and OSAS through the sequential analyses of genetic linkage and association. The purpose of this review is to summarize some of remarkable molecular advances in sleep and sleep disorders, thereby providing a greater understanding of the complex sleep processes, and a platform for future therapeutic interventions. (C) 2009 Wiley-Liss, Inc.
Keywords: sleep; genetic; narcolepsy; restless legs syndrome; obstructive sleep apnea syndrome